The Principles of Home Care for Patients with Stroke: An Integrative Review - Somayeh Bahadoram; Narges Arsalani; Masoud Fallahi-Khoshknab; Farahnaz Mohammadi-Shahbolaghi; Asghar Dalvandi (Wolters Kluwer Medknow Publications, 2024)
Background: Patients With Stroke (PWS), like patients with other chronic health conditions, need long-term care in home settings. Patient transfer from hospital to home is associated with challenges such as care quality impairment and ineffective patient need fulfillment. The aim of this study was to assess the principles of Home Care (HC) for PWS. Materials and Methods: This integrative review was conducted in 2023 using the method recommended by Whittemore and Knafl. The Web of Science, Google Scholar, ScienceDirect, ProQuest, Scopus, Cumulative Index to Nursing and Allied Health Literature, PubMed, and specific databases for stroke care guidelines were searched to find relevant articles published between 2010 and 2023. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was used for document screening and selection. The data were analyzed using the constant comparison method. Results: Primarily, 2608 documents were retrieved, and 22 of them were included in data analysis. The principles of HC for PWS were categorized into six main categories: principles of transition from hospital care to HC, principles of assessment for HC, principles of education for HC, principles of designing an HC plan, principles of HC measures, and principles of discharge from HC centers. Conclusions: The present study provides a detailed overview of the principles of HC for PWS, which can be used to develop standard guidelines and improve the quality of HC for PWS.